Bone metastases in pheochromocytomas and paragangliomas: a narrative review of presentation, diagnosis and management - Contreras-Saldarriaga, Jorge Eduardo; Loaiza-Alzate, Melissa (Frontiers in Endocrinology, 2025)
BackgroundBone metastases (BM) are a frequent and clinically relevant manifestation in patients with metastatic pheochromocytomas and paragangliomas (mPPGL).ObjectiveThis narrative review aims to summarize the current understanding of the pathophysiology, epidemiology, clinical presentation, complications, quality of life impact, and management of BM in mPPGL.SummaryBone and lymph nodes are among the most common metastatic sites in malignant PPGL. Skeletal involvement—particularly in paragangliomas—is associated with a high incidence of skeletal-related events (SREs), including pathological fractures, spinal cord compression, and pain. These complications lead to reduced mobility, loss of independence, and decreased survival. Advances in functional and anatomical imaging have improved detection, but optimal management remains complex and requires a multidisciplinary approach.ConclusionRecognizing patients at higher risk and understanding the biological mechanisms underlying bone dissemination are essential to optimize diagnosis, prevent SREs, and improve outcomes in this rare and challenging disease.